(untitled) (Praxis Educativa, 2016)
This year, Argentina is commemorating both the 40th anniversary of the civic-military coup d’état, and the recuperation of institutionalism. From this complex setting, (focused on recuperation of democracy), this work aims atinquiring about certain continuities and ruptures which keep co-existing or “ruling” to the interior of the political re-socialization dynamics, in the institutional political life of many of our Universities. We are basically interested in debating, highlighting and decrystalizing power relations which may be captive, deeply rooted, or constrained to logics from the past or “old bad practices” policies. We are convinced that re-considering them -along with their logical correlates of action, omission, presence and absence in institutional life- keeps being a core issue that could lead to renew our commitment to institutions and democracy